The effectiveness of active shielding of magnetic field with circular spacetime characteristic and with different shielding coils spatial positions - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V. (Національний технічний університет "Харківський політехнічний інститут", 2020)
Computer simulation and field experimental research results of two degree of freedom robust two circuit system of active shielding of magnetic field, generated by overhead power lines with «triangle» type of phase conductors arrangements and with different shielding coils spatial positions are given. The possibility of initial magnetic flux density level reducing and system sensitivity to the plant parameters uncertainty reducing is shown.

Приводятся результаты компьютерного моделирования и полевых экспериментальных исследований комбинированной робастной двухконтурной системы активного экранирования магнитного поля, генерируемого воздушной линией электропередачи с треугольным подвесом проводов, и с различным пространственным расположением экранирующих обмоток. Показана возможность снижения уровня индукции исходного магнитного поля внутри экранируемого пространства и снижения чувствительности системы к неопределенностям параметров объекта управления.
Keywords: overhead power lines with «triangle» type of phase conductors arrangements; computer simulation; field experimental research; воздушная линия электропередач; компьютерное моделирование; полевые экспериментальные исследования